Lehman Brothers & General Motors: contrasting models of failure - Birkinshaw, Julian (Henry Stewart Talks, 2017)
The case study looks at the two contrasting company cultures at Lehman Brothers and General Motors, and suggests that’s it’s not any particular management style that allows a company to fail but rather the rigid adherence to any one particular style.